INFLUENCE OF THE CUSTOMS UNION ON ECONOMIC DEVELOPMENT OF KAZAKHSTAN. BASIC PROBLEMS AND PROSPECTS - G. G. Rahmatulina (Модернизация, инновация, развитие, 2016)
Examination of the Kazakhstan economy functioning results for the first year of the Customs Union existence proves that along with eliminationof some barriers in the trade between the alliance participating countries, difficulties arose owing to disaccord in the tariff policy (particularly related to railway transportation of goods), necessity to prepare new documents, etc., that negatively infl uence activities of Kazakhstan companies. In order to remove these difficulties, intensive mutual efforts should be taken by governmental authorities of all TC participating countries, opinion of respective business communities having to be compulsorily taken into account.